2020
DOI: 10.1007/s11104-020-04528-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of climate on decomposition of cattle, sheep and goat manure in Kenyan tropical pastures

Abstract: Aims Decomposition of manure deposited onto pasture from grazing animals represents an important process for carbon (C) and nitrogen (N) cycles in grassland systems. However, studies investigating manure decomposition are scarce; especially in sub-Saharan Africa (SSA). Methods In this study, we measured decomposition of three types of animal manure (cattle, sheep, goat) over >1 year using litter bags at four climatically different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 79 publications
1
16
0
1
Order By: Relevance
“…At the dry climate of KAZA, the C loss from the dung will largely occur as CO 2 , or it is taken away by small animals such as beetle and termites (Andriuzzi & Wall, 2018). Yet, there are also continued dung‐C reimports, constantly replenishing the pool and compensating the losses (Zhu et al, 2020), that is, under steady‐state conditions the amount of C in the dung is withdrawn from the atmosphere irrespectively of the dung turnover time. Future studies should thus include the amount of dung C into climate change mitigation calculations, because even this labile dung C may add to climate change mitigation if the decomposing dung is continuously replaced by fresh one.…”
Section: Discussionmentioning
confidence: 99%
“…At the dry climate of KAZA, the C loss from the dung will largely occur as CO 2 , or it is taken away by small animals such as beetle and termites (Andriuzzi & Wall, 2018). Yet, there are also continued dung‐C reimports, constantly replenishing the pool and compensating the losses (Zhu et al, 2020), that is, under steady‐state conditions the amount of C in the dung is withdrawn from the atmosphere irrespectively of the dung turnover time. Future studies should thus include the amount of dung C into climate change mitigation calculations, because even this labile dung C may add to climate change mitigation if the decomposing dung is continuously replaced by fresh one.…”
Section: Discussionmentioning
confidence: 99%
“…Cow excreta hold a large amount of water, facilitating the bacterial colonies to decompose down and give off their nutrients slowly [ 5 ]. However, it is also reported that cow excreta decompose more rapidly than goat excreta [ 29 ]. It may be due to the composition of food (grass).…”
Section: Discussionmentioning
confidence: 99%
“…Two plausible reasons could explain this phenomenon. Firstly, the decomposition rate of animal manure or plant materials returned to the field is generally less than a half, which is lower than that of chemical fertilizer and will reduce the soil H + production [18]; Secondly, the organic acids produced by the compost can form complexes with the exchangeable aluminum in soil [19].…”
Section: Introductionmentioning
confidence: 99%